1998
DOI: 10.1128/aac.42.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Dicaffeoylquinic and Dicaffeoyltartaric Acids Are Selective Inhibitors of Human Immunodeficiency Virus Type 1 Integrase

Abstract: Current pharmacological agents for human immunodeficiency virus (HIV) infection include drugs targeted against HIV reverse transcriptase and HIV protease. An understudied therapeutic target is HIV integrase, an essential enzyme that mediates integration of the HIV genome into the host chromosome. The dicaffeoylquinic acids (DCQAs) and the dicaffeoyltartaric acids (DCTAs) have potent activity against HIV integrase in vitro and prevent HIV replication in tissue culture. However, their specificity against HIV int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(134 citation statements)
references
References 55 publications
2
131
0
1
Order By: Relevance
“…In addition, some dicaffeoylquinic acids derived from another plant have been reported to possess anti-HIV activity (Cos et al, 2004). It was suggested that the likely anti-HIV target of dicaffeoylquinic acids could be the HIV-1 integrase (McDougall et al, 1998;Zhu et al, 1999). It was also reported that HIV strains, which were made resistant to the dicaffeic acid derivatives, contained several mutations in its envelope glycoprotein gp 120.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, some dicaffeoylquinic acids derived from another plant have been reported to possess anti-HIV activity (Cos et al, 2004). It was suggested that the likely anti-HIV target of dicaffeoylquinic acids could be the HIV-1 integrase (McDougall et al, 1998;Zhu et al, 1999). It was also reported that HIV strains, which were made resistant to the dicaffeic acid derivatives, contained several mutations in its envelope glycoprotein gp 120.…”
Section: Resultsmentioning
confidence: 96%
“…50 In follow-up studies, dicaffeoylquinic acids (DCQAs) and dicaffeoyltartaric acids (DCTAs) were found to inhibit HIV-1 integrase at concentrations between 0.15 and 0.84 mM, and HIV replication at concentrations between 2 and 12 mM; no inhibition of gp120 binding to CD4 was noted at concentrations up to 80 mM. 51 Likewise, no inhibition of reverse transcription or RNase H was noted, and it was concluded 51 that the DCQAs and DCTAs act as speci®c integrase inhibitors, and that their activity against integrase is consistent with their observed anti-HIV activity in cell cultures. That the integrase would be an``excellent'' target for combination chemotherapy of HIV infection was further ascertained by combination experiments where L-chicoric acid, the putative integrase inhibitor, was combined with a protease inhibitor (AG1350) and zidovudine.…”
Section: C U R C U M I N C U R C U M I N a N A L O G U E S D mentioning
confidence: 99%
“…DNA integration is carried out by integrase, so HIV-1 integrase represents a key area in developing new antiretroviral therapy [14]. And as no cellular homologue of HIV-1 integrase has been described, this kind of potential inhibitors for HIV-1 integrase could be relatively nontoxic [11,[15][16][17][18][19]. DCQAs have been confirmed to be an effective HIV-1 integrase inhibitor [20] by selectively inhibiting HIV-1 integrase irreversibly toward its conserved amino acid residues in the central core domain of catalysis and preventing HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%